Sejarah Perkembangan Penjaminan Halal di Indonesia - Nahlah - Nahlah; Siradjuddin Siradjuddin; Ahmad Efendi; I Nyoman Budiono; A. Ika Fahrika (Jurnal Ilmiah Ekonomi Islam, 2023)
One of the rules in Islam is not to consume or use anything that Islam forbids. This world is not only inhabited by people who are Muslims. Many religions and beliefs other than Islam do not forbid some foods that Muslims consider unclean, such as pork and its derivatives or slaughtering meat without mentioning the name of Allah. In addition, there is no prohibition for other religions to market their products in the Muslim environment. Therefore, Muslims need halal guarantees for the products they want to buy. The purpose of this research is to find out how the process of protecting Muslim consumers in Indonesia from products that are not halal. This research method is normative juridical with a qualitative approach. A literature review was carried out on laws and regulations, which were then analyzed descriptively. Secondary data from journals and websites is also a source of study. The study results show that government and non-government parties have shown severe concern in protecting halal product guarantees for Muslim consumers in this country by drafting halal assurance regulations in stages, starting from the labeling "no pork", voluntary halal labeling to the obligation of halal certification for business actors in this country